Structural insights into Salinosporamide A mediated inhibition of the human 20S proteasome - Sülzen, Hagen; Fajtova, Pavla; O'Donoghue, Anthony J; Boura, Evzen; Silhan, Jan (bioRxiv, 2025)
The 20S proteasome, a critical component of the ubiquitin-proteasome system, plays a central role in regulating protein degradation in eukaryotic cells. Marizomib (MZB), a natural γ-lactam-β-lactone compound derived from Salinispora tropica, is a potent 20S proteasome covalent inhibitor with demonstrated anticancer properties. Its broad-spectrum inhibition of all three proteasome subunits and ability to cross the blood-brain barrier has made it a promising therapeutic candidate for glioblastoma. Here, we present the cryo-EM structure of the human 20S proteasome in complex with MZB at 2.55 Å resolution. This structure reveals the binding mode of MZB to all six catalytic subunits within the two β-rings of the 20S proteasome, providing a detailed molecular understanding of its irreversible inhibitory mechanism. These findings explain the therapeutic potential of MZB at the molecular level and highlight marine-derived natural products in targeting the proteasome for anticancer treatment.